EDUKASI PEREMPUAN DALAM BERKEBUN UNTUK MENINGKATKAN KETAHANAN EKONOMI PADA MASA COVID-19 - Gusniarti,; Afni Rasyid, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has an impact on a new food crisis by disrupting food production and distribution which can threaten people's lives because they do not have access to sufficient food. Carrying out agricultural activities by utilizing their own land, namely planting crops that are daily necessities, such as vegetables, chilies, tomatoes and others are the right solution to increase economic resilience during the Covid-19 period and women have a very big role in it. The purpose of this Community Service is to provide education and assistance to the Aisyiyah Family and Aisyiyah sympathizers in proper farming, starting from providing the right planting media by making compost, seeding, planting and caring for plants by dealing with Plant Pest Organisms (OPT). Method: Education and Mentoring. The number of participants was 42 people consisting of 82% of Aisyiyah Families in South Tangerang City and 18% were Autonomous Organization. Meanwhile, the partner of this activity is the Economic and Employment Council of the South Tangerang City PDA. Results: Participants gained a clear understanding of the preparation of planting media, seeding and planting as well as the care and control of pests. The results of this education were practiced in their respective homes and are expected to be able to educate other people. Conclusion: Gardening in your own yard can be said to be quite effective in helping or at least reducing costs in household especially during this Covid-19 period. However, women often experience failure in gardening, because they do not pay attention to the planting media and their care. The theme presented in this mentoring really helped the problems faced by women in gardening in their own yard.